Anti-oxidant and anti-inflammatory effects of new bibenzyl derivatives from Dendrobium parishii in hydrogen peroxide and lipopolysaccharide treated RAW264.7 cells. (April 2018) - Kongkatitham, Virunh; Muangnoi, Chawanphat; Kyokong, Napat; Thaweesest, Wuttinont; Likhitwitayawuid, Kittisak; Rojsitthisak, Pornchai; Sritularak, Boonchoo
Graphical abstract: Highlights: Two new and five known compounds were isolated from Dendrobium parishii . (−)-Dendroparishiol (2 ) exhibited potent antioxidant and anti-inflammatory effects. Compound2 enhanced SOD, GPx and CAT activities in H2 O2 treated RAW264.7 cells. Compound2 decreased NO and TNF-α secretion in LPS treated RAW264.7 cells. Compound2 reduced iNOS and COX-2 expression in LPS treated RAW264.7 cells. Abstract: Oxidative stress and inflammatory responses are the main causes of various diseases and disorders. To prevent these incidents, antioxidant and anti-inflammatory agents are needed. Dendrobium parishii, known in Thai as "Ueang Khrang Sai San" was studied for chemical constituents by solvent extraction, followed by column chromatography. Seven compounds including two new (1–2 ) and five known compounds (3 –7 ) were isolated and screened for antioxidant activity using DPPH, ORAC and deoxyribose assays. The new compound (compound2 ) showed the highest antioxidant activities and was further evaluated for its antioxidant and anti-inflammatory effects, as well as mechanisms of action in RAW264.7 murine macrophage cells under oxidative stress and inflammation induced by hydrogen peroxide (H2 O2 ) and lipopolysaccharide (LPS), respectively. Compound2 at 12.5, 25 and 50 μg/mL significantly decreased ROS in H2 O2 treated RAW264.7 cells in a dose dependent manner and enhanced antioxidant enzyme (SOD, GPx and CAT) activities. For the anti-inflammatory activity, compound2 reduced the expression of iNOS and COX-2 in LPS treated RAW264.7 cells. The results indicate that compound2 has the potential to be developed as an antioxidant and anti-inflammatory agent.